2017
DOI: 10.1007/s11356-017-8913-9
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of polycyclic aromatic hydrocarbons and n-alkanes in the soil-sediment profile of Jianghan Oil Field, China

Abstract: Surface soil in oil exploration area always contains high contents of polycyclic aromatic hydrocarbons (PAHs) and n-alkanes. To investigate the migration possibility of PAHs and n-alkanes from surface through aquitard and aquiclude to aquifer, the distribution, together with the source apportionment using several indicators, such as composition pattern, fluoranthene/(fluoranthene+pyrene) (Flt/(Flt+Pyr)), anthracene/(anthracene+phenanthrene) (Ant/(Ant+PA)), and the carbon preference index (CPI) of n-alkanes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In samples B and C, the calculated CPI values are above 2, which indicates a natural input of hydrocarbons [6, 30, 39]. On the other hand, based on a CPI value of around 1 as well as the dominance of n ‐alkanes with an odd number of C atoms, an anthropogenic source of pollution in all samples can be confirmed [17, 22, 23]. Based on previous findings, this leads to the conclusion that the samples contain an organic substance of native origin with intensive input from anthropogenic sources.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In samples B and C, the calculated CPI values are above 2, which indicates a natural input of hydrocarbons [6, 30, 39]. On the other hand, based on a CPI value of around 1 as well as the dominance of n ‐alkanes with an odd number of C atoms, an anthropogenic source of pollution in all samples can be confirmed [17, 22, 23]. Based on previous findings, this leads to the conclusion that the samples contain an organic substance of native origin with intensive input from anthropogenic sources.…”
Section: Resultsmentioning
confidence: 72%
“…Odd C-number 1.00-4.80 [42] Pichavaram mangroves, India n-C11-n-C37 Various 0.75-8.63 [40] Central Alaska, USA n-C19-n-C35 Odd C-number 2.20-21.00 [38] Suez Gulf, Egypt n-C10-n-C40 Mainly even C-number 0.62-1.95 [43] Lake Middle Marviken, Sweden n-C15-n-C31 Odd C-number 3.60-8.00 [39] Banja Luka, Bosnia and Herzegovina n-C14-n-C39 Odd C-number 1.12-1.48 This study of C atoms, an anthropogenic source of pollution in all samples can be confirmed [17,22,23]. Based on previous findings, this leads to the conclusion that the samples contain an organic substance of native origin with intensive input from anthropogenic sources.…”
Section: N-c17-n-c36mentioning
confidence: 63%
See 1 more Smart Citation
“…Fingerprint profiles of the suspected sources in the samples were examined graphically by reviewing PAH concentrations of parent and alkylation abundance to display their relative slope (decrease, increase, or bell-shaped). Diagnostic ratios were used to identify a probable match (Ma et al 2017; Ranjbar Jafarabadi et al 2017a). The diagnostic PAH ratios (Table SM-2) were used to determine petrogenic or pyrogenic sources and potential input sources (Short et al 1998 and Crane 2014).…”
Section: Methodsmentioning
confidence: 99%
“…It indicated that the strong permeable stratum is conducive to the rapid transport of organic pollutants, and the particulate matter may be the leading carriers of HMW-PAHs (Levy et al 2017). While in the weak permeable aquifer, HMW-PAHs are easily hindered and adsorbed by carbonate rock debris and deposited in karst conduit (Ma et al 2017). The MLRA results showed that the transport of PAHs from both the soil and spring water could explain 20.6% and 96.2% (R 2 =0.206, 0.962) of the PAHs in the spring sediments of MGQ and YQD spring systems, respectively.…”
Section: Pahs Transport Characteristics In Typical Karst Spring Systemsmentioning
confidence: 99%